Multipath Virtual Sink Architecture for Underwater Sensor Networks - SEAH, Winston K. G. (Institutional Knowledge at Singapore Management University, 2010)
Underwater sensor networks promise new opportunities for exploration of the oceans, which cover more than 70% of the earth's surface. Researchers envision the deployment of dense networks of untethered sensors underwater for data acquisition to better understand the underwater environment, while miliary and security forces see the great potential of using this technology for mine reconnaissance, intrusion detection, and surveillance. Currently, acoustic communications is the only physical layer technique considered viable, and this renders many of the schemes that have been designed for terrestrial sensor networks using radio frequency commnications unusable under water. Key challenges include the long propagation delay of the acoustic channel and the severely fluctuating link conditions. The generally adopted single-sink architecture, be it static of mobile, is extremely vulnerable to poor and fluctuating channel conditions, especially when it occurs anywhere en route to the sink. We propose a novel virtual sink approach with multipath data delivery to overcome the adverse link conditions. Multipath tends to lead to contention near the sink, which we avoid with the virtual sink design involving a group of spatially diverse physical sinks. Hence, we are able to exploit the reliability achieved from redundancy provided by multipath data delivery while mitigating the contention. In this chapter, we shall present the proposed architecture and validate its efficacy by studying the performance of relevant data delivery schemes through analysis and simulations. We conclude with a discussion of potential use scenarios and applications that can benefit from this architecture, and future work.